Association between rainfall intensity and level of road damage - Tamilvanan, Muniandi (2016)
Rainwater is found to be the major reason contributing to severe road damage in Malaysia. There is one strong hypothetical theory that associates this serious issue which is, rainfall intensity defines the level of road damage. Flood water and prolonged heavy rainfall are endangering road surface through delamination, cracking and potholes. The study is conducted to distinguish between years in terms of rainfall event and defects in local pavements. After that, correlation between rainfall intensity and quantity of road damage was evaluated. To conduct this study, data for two segments are collected, which are on rainfall intensity and volumes of damaged sections from the year 2014 to 2015 along two routes, Jalan Sungai Lembing and Jalan Padang Lalang-Tanjung Lumpur-Kg Bahru. Correlation and Regression Analysis were conducted to examine if there is a proven relation between rainfall intensity and volume of damaged section at each study location in each year. It is shown that both study areas share positive and negative correlation between rainfall intensity and percentage of road damage with no associations that were proven. T-test on paired samples for means was conducted to distinguish between years in terms of rainfall intensity and volume of damaged sections within the same location. Volume of road damage has increased in the year 2015 while the rainfall intensity remained same throughout the time period of both years. T-test on independent two samples for means was conducted to distinguish between two different study areas in terms of rainfall intensity and volume of damaged sections within the same year. From the analysis done in each year at both locations, only Jalan Sungai Lembing is exposed to higher road damage while the rainfall intensity remained same at both locations. It is proven that rainfall intensity did not leave any impact on the volume of damaged section. Conclusively, there are no statistical evidences to support the sole impact of rainfall intensity towards road damage. It is also found that there might be other factors which are causing road damage in association with rainfall intensity.